A scalable and sensitive steatosis chip with long-term perfusion of in situ differentiated HepaRG organoids. (August 2021) - Teng, Yao; Zhao, Zixuan; Tasnim, Farah; Huang, Xiaozhong; Yu, Hanry
Abstract: Nonalcoholic fatty liver disease (NAFLD) is a significant liver disease without approved therapy, lacking human NAFLD models to aid drug development. Existing models are either under-performing or too complex to allow robust drug screening. Here we have developed a 100-well drug testing platform with improved HepaRG organoids formed with uniform size distribution, and differentiated in situ in a perfusion microfluidic device, SteatoChip, to recapitulate major NAFLD features. Compared with the pre-differentiated spheroids, the in situ differentiated HepaRG organoids with perfusion experience well-controlled chemical and mechanical microenvironment, and 3D cellular niche, to exhibit enhanced hepatic differentiation (albumin + cells ratio: 66.2% in situ perfusion vs 46.1% pre-differentiation), enriched and uniform hepatocyte distribution in organoids, higher level of hepatocyte functions (5.2 folds in albumin secretion and 7.6 folds in urea synthesis), enhanced cell polarity and bile canaliculi structures. When induced with free fatty acid (FFA), cells exhibit significantly higher level of lipid accumulation (6.6 folds for in situ perfusion vs 4.4 folds for pre-differentiation), altered glucose regulation and reduced Akt phosphorylation in the organoids. SteatoChip detects reduction of steatosis when cells are incubated with three different anti-steatosis compounds, 78.5% by metformin hydrochloride, 71.3% by pioglitazone hydrochloride and 66.6% by obeticholic acid, versus the control FFA-free media (38% reduction). The precision microenvironment control in SteatoChip enables improved formation, differentiation, and function of HepaRG organoids to serve as a scalable and sensitive drug testing platform, to potentially accelerate the NAFLD drug development. Graphical abstract: Image 1